DESIGN OF TSUNAMI DETECTOR BASED SORT MESSAGE SERVICE USING ARDUINO AND SIM900A TO GSM/GPRS MODULE - Puput Dani Prasetyo Adi; Rahman Arifuddin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2018)
Tsunamis are one of the most unforeseen natural disasters, factors or signs of a tsunami occurring among others is the sudden reflux of seawater which is due to the broken plate of the underlying sea floor receding water, the plate fault is caused by seismic ground-based earthquakes, areas ever experienced a previous fault is likely to occur in the same quake place this is because the slabs can not coalesce or return like the original. for it needed a prototype system that can detecting the early detection of a tsunami that could cost many lives. The prototype system created is equipped with a fibration sensor to detect vibration and Ultrasonic sensors to detect distances, after of some varible detected then the data will be transmitted remotely via SIM900A as GSM / GPRS ModuleDOI : https://doi.org/10.26905/jeemecs.v1i1.1982